ADVOCACY, SUPPORT FOR RESOURCES, AND THE ROLE OF COMMUNITY LEADER TOWARD MOTHER’S ATTITUDE ON EXCLUSIVE BREASTFEEDING PROGRAM - Mufdlilah Mufdlilah; Achmad Arman Subijanto; Muhammad Akhyar; Endang Sutisna (Belitung Nursing Journal, 2016)
Background: Indonesia’s Health Law No. 36 year 2009 Section 128 states that every baby has the right to exclusively breastfed from birth for six months. The law also stipulates that during breastfeeding, the family, the government, local governments, and public should support mothers with the provision of time and special facilities. Objective: This study aims to analyze factors related to exclusive breastfeeding program, especially indicators that can explain advocacy to stakeholders, support for resources and the role of community leader toward mother’s attitude on exclusive breastfeeding program. Methods: It was a quantitative study employed a cross-sectional approach and involved 185 mothers in Sleman district who have children aged 6-12 months. Results: Written support in the form of decree significantly contributed to the formation of advocacy factors conducted by exclusive breastfeeding program manager to the village stakeholders, whilst the provision of infrastructure and village fund did not support in creating factor of advocacy. The support from resources and the role of community leader can contribute the provision of infrastructure around 54% whilst mothers’ attitudes toward exclusive breastfeeding devoted a great share to mother’s practice. Conclusion: Advocacy for exclusive breastfeeding to the village stakeholders is expected to contribute in the form of written support (decree), providing the fund from the village budget, and providing the infrastructure. The support from resources and the role of community leaders influence advocacy and attitude of mothers on exclusive breastfeeding.